2013
DOI: 10.1021/bm4009606
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Cross-Linkable Hydrogel of Hyaluronan Produced via Copper-Free Click Chemistry

Abstract: Injectable hydrogels are useful in biomedical applications. We have synthesized hyaluronic acids chemically modified with azide groups (HA-A) and cyclooctyne groups (HA-C), respectively. Aqueous HA-A and HA-C solutions were mixed using a double-barreled syringe to form a hydrogel via strain-promoted [3 + 2] cycloaddition without any catalyst at physiological conditions. The hydrogel slowly degraded in PBS over 2 weeks, which was accelerated to 9 days by hyaluronidase, while it rapidly degraded in a cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 53 publications
3
104
0
Order By: Relevance
“…The in vitro gelation, morphologies, equilib- 34 rium swelling, compressive modulus and degradation of the composite hydrogels were examined. The 35 potential of the metal-free hydrogel as a cell scaffold was demonstrated by encapsulation of human adi- 36 pose-derived stem cells (ASCs) within the gel matrix in vitro. Cell culture showed that this metal-free 37 hydrogel could support survival and proliferation of ASCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro gelation, morphologies, equilib- 34 rium swelling, compressive modulus and degradation of the composite hydrogels were examined. The 35 potential of the metal-free hydrogel as a cell scaffold was demonstrated by encapsulation of human adi- 36 pose-derived stem cells (ASCs) within the gel matrix in vitro. Cell culture showed that this metal-free 37 hydrogel could support survival and proliferation of ASCs.…”
mentioning
confidence: 99%
“…Presently, the SPPC has been employed to graft bioactive 86 peptides to PEG hydrogels for molecular patterning [33,34]. Also, 87 Takahashi et al chemically modified hyaluronan with azide and 88 cyclooctyne groups to prepare an in situ crosslinked hyaluronan 89 hydrogel [35]. Although the formed hydrogel was biocompatible, 90 it showed fast hydrolytic degradation that may prevent its use in 91 tissue engineering.…”
mentioning
confidence: 99%
“…Recently, the even more selective native chemical ligation which involves a thioesther and an N -terminal cysteine has been used for the formation of hydrogels [ 102 ]. Also copper free click-reactions are now being developed, which have a good substrate specifi city and improved reaction kinetics [ 103 ]. Alternatively, enzymatic reactions which are known to have a very high substrate specifi city have been used to form hydrogels [ 102 ] being highly compatible with the preservation of active growth factors.…”
Section: Cross-linking Mechanismsmentioning
confidence: 99%
“…By chemical modi cation, polymers can be crosslinked to form large polymeric networks, 14,106,123,124 or conjugated with other functional molecules that e.g. provide self-assembling properties, 75,110,111 or increase their bioactivity.…”
Section: Modi Cation Of Polymers and Conjugation With Peptidesmentioning
confidence: 99%